PENGARUH ELECTRONIC WORD OF MOUTH DAN TOURIST MOTIVATION TERHADAP SATISFACTION SERTA REVISIT INTENTION - Aitarra, Galang; Pujiastuti, Eny Endah; Nur Utomo, Hastho Joko (Jurnal Ilmu Administrasi dan Bisnis, 2020)
Revisit intention in tourism marketing is the hope of destination managers for the sustainability of their destinations. Revisit intention of tourist areas is influenced by many factors. The problems and objectives of this study are the effect of electronic word of mouth and tourist motivation on satisfaction and revisit intention. The research location is on the beach of Krakal Gunung Kidul, Yogyakarta. Tourists who have visited  the  destination  for  the  first  time  become  the  research  samples.  The  data  collected  from  120 respondents  with questionnaires, dan  analyzed by  SEM AMOS. The conclusion  of this study  shows  that electronic word of mouth and also tourist motivation have a significant effect on satisfaction, electronic word of mouth has a significant effect on revisit intention, either on tourist motivation too, also there was a  significant  effect  from  satisfaction  on  revisit  intention.  The  limitation  of  this  study  which  the  sample criteria is to general, it is need more specific, such as by age, then the bias will be more minimize. Further research hoped that it can examine other variables like attractiveness, facilities and tourist experience.